Sphingolipids and Epoxidized Lipid Metabolites in the Control of Gut Immunosurveillance and Allergy - Kunisawa, Jun; Kiyono, Hiroshi (Frontiers in Nutrition, 2016)
The intestinal immune system ingeniously balances the distinct responses of elimination and tolerance of non-self-substances for the creation and maintenance of homeostatic environments. Accumulating evidence has recently shown that various lipids, including dietary one, are involved in the regulation of intestinal immunity and are associated with biophylaxis and immune disorders. Recent advances in the lipidomics allow the identification of novel pathways of lipid metabolism and lipid metabolites for the control of intestinal immunity. In this paper, we describe the effects and functions of lipids, especially sphingolipids and new lipid metabolites originated from dietary oil on the immunomodulation and on the development and pathogenesis of allergic diseases in the intestine.